Poliedros regulares e semirregulares - Pafume, Mateus Rodrigo (Universidade Federal de São Carlos, 2021)
The subject os this study is a retelling of the Steps I and II of the book “Matem@tica na Pr@tica, Geometria espacial: módulo 2”, by Cláudio Carlos Dias, João Carlos Vieira Sampaio, Marlusa Benedetti da Rosa, Tomás Edson Barros. These modules are about Regular or Semi-regular (archimedean) polyedra, wich are solids obtained through the techniques of truncation or snub. The main objective pf this study is to produce a theoretical material, with historical and philosophical elements about Regular and Semi-regular polyhedra, so it can be used for undergraduate students in Mathematics.
Regular and semiregular polyhedra
Keywords: Poliedros; Poliedros Regulares; Poliedros Semirregulares; CIENCIAS EXATAS E DA TERRA::MATEMATICA